Insight into the Formation and Reactivity of Framework‐Bound Methoxide Species in H‐ZSM‐5 from Static and Dynamic Molecular Simulations. Issue 7 (11th June 2014) - Van der Mynsbrugge, Jeroen; Moors, Samuel L. C.; De Wispelaere, Kristof; Van Speybroeck, Veronique
Abstract Framework‐bound methoxides occur as intermediates in the stepwise mechanism for zeolite‐catalyzed methylation reactions. Herein, the formation of methoxides from methanol or dimethyl ether in H‐ZSM‐5 is investigated by a combination of static and dynamic simulations, with particular focus on the effect of additional water and methanol molecules on the mechanism and kinetics. Metadynamics simulations allow partitioning the reaction path into distinct phases. Proton transfer from the zeolite to the reactants is found to be the rate‐limiting phase in the methoxide formation. Additional methanol molecules only assist the proton transfer in the methoxide formation from methanol, whereas the reaction from dimethyl ether does not benefit from methanol assistance. Once formed, methoxides are found to be as reactive toward alkene methylation as methanol and dimethyl ether.